Klf9 Loss of Function Protects Against Glucocorticoids Induced Skeletal Muscle Wasting - Yujie Zhang; Jingran Hao; Yueyao Feng; Tongtong Qiu; Jinjin Wu; Xuenan Zhou; Heng Fan; Yongsheng Chang (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Glucocorticoids (GCs) are the most important and frequently used class of anti‐inflammatory drugs. However, the mechanisms underlying excessive glucocorticoid‐mediated induction of muscle atrophy remain incompletely understood. Methods We generated skeletal muscle‐specific Klf9 transgenic mice (mKlf9TG) and skeletal muscle‐specific Klf9 knockout mice (Klf9mlc−/−). The body weight, tissue weight, body composition, grip strength, running distance and muscle fibre cross section of mKlf9TG, Klf9mlc−/− mice and their littermate controls were examined. Expression of genes related to muscle protein synthesis and degradation pathways were also tested in the mKlf9TG mice, Klf9mlc−/− mice and their littermate controls. We performed Klf9 gain‐ or loss‐of‐function studies in differentiated C2C12 myotubes using lentiviruses encoding Klf9 or the shRNA specific to Klf9 in vitro. Luciferase reporter gene assay and ChIP assay were performed to explore the molecular mechanism of Klf9 action. Klf9mlc−/− and Klf9fl/fl mice were treated with dexamethasone (Dex). Multiple genetic and pharmacological approaches were also used to investigate the intracellular signalling cascades underlying the Dex/Klf9‐ediated skeletal muscle wasting. Results Skeletal muscle Klf9 gene expression was significantly upregulated by Dex (p < 0.05 or p < 0.01 vs. vehicle group). Compared with littermate control mice (R‐loxP), mKlf9TG mice exhibited decreased skeletal muscle mass (TA 0.101 ± 0.018 vs. 0.040 ± 0.007 g, p < 0.001) and impaired grip strength (forelimb 157.4 ± 3.7 vs. 93.45 ± 9.8 and four limbs 255.3 ± 23.1 vs. 170.1 ± 36.2, p < 0.001). Conversely, compared with Klf9fl/fl, Klf9mlc−/− mice exhibited increased skeletal muscle mass (TA 0.103 ± 0.012 vs. 0.123 ± 0.005 g, p < 0.001) and enhanced grip strength (forelimb 110.3 ± 5.8 vs. 156.8 ± 10.0 and four limbs 155.5 ± 6.3 vs. 226.5 ± 19.7, p < 0.001). Skeletal muscle Klf9 deficiency alleviated muscle atrophy induced by acute high‐dose Dex treatment (p < 0.001). Mechanistically, Klf9 induces the expression of myostatin (Mstn) and muscle atrophy F‐box (MAFbx) by directly binding to and activating the transcription of their promoters. Treatment of AAV‐MSTN reduced the increased grip strength of Klf9mlc−/− mice (forelimb 143.5 ± 22.3 vs. 118.8 ± 3.1 and four limbs 249.8 ± 24.7 vs. 208.7 ± 9.0, p < 0.001). Conclusions In summary, our study provides novel insights into the mechanisms underlying GC‐induced muscular atrophy and reveals that skeletal muscle induction of Klf9 expression is a mechanism underlying GC therapy‐induced muscle loss. Thus, targeting Klf9 may offer novel approaches to the treatment of skeletal muscle wasting diseases.